Modernizing Batik Clothes for Community Enterprises Using Creative Design and Colorimetry - Suvita Kaewareelap; Yaowarat Sirisathitkul; Chitnarong Sirisathitkul (Emerging Science Journal, 2021)
The objective of this study was to modernize batik clothes, a cultural heritage of Southeast Asia, through creative design, color characterization, and collection presentation. Three community enterprises from the southern regions of Thailand participated in designing batik motifs based on their local identities. The pattern of the first manufacturer group was influenced by stones and ancient beads of vivid orange and blue shades. The second community was inspired by the nearby sea, resulting in ocean blue, white, and emerald green colors on batik fabrics. Floras in the south of Thailand dominated the design of the final manufacturer group. Smartphone colorimetry was then used to characterize the batik fabrics. It was demonstrated that this proposed color quantification was not confined to the laboratory, and could easily be carried out by vendors or customers. The collaboration encouraged local batik artisans to use a variety of inspirations, new tools, as well as professional design and production methods. To introduce modernized batik to the public, collections of these newly designed clothes were displayed in a fashion show staged under the theme “Southern Chic.” The presentation of Thai batik clothes in seasonal collections highlighted the transformations of local manufacturers and products with increasing appeal to younger people. In addition to conservation and commercial advantages, the modernized approach is accessible and attractive for education purposes, engaging students in cultural heritage. Doi: 10.28991/esj-2021-01319 Full Text: PDF